EXTRACTION OF JOJOBA OIL USING VARIOUS CONCENTRATIONS OF TWO DIFFERENT SOLVENTS - & et al., Abdulraheem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this study was extraction of jojoba oil using different solvents. A mixture of water-hexane and water-ethanol are used as solvents to extract jojoba oil in a batch extraction process and compared with a pure solvent extraction process. The effects of particle size of crushed seeds, solvent-to-water ratio and time on jojoba oil extraction were investigated. The best recovery of oil was obtained at the boiling temperature of the solvent and four hour of extraction time. When seed particle size was 0.45 mm and a pure ethanol was used (45% yield of oil extraction), whereas, it was 40% yield of oil at 25% water- hexane mixture. It was revealed that the water-ethanol and water-hexane mixtures have an effect on the oil extraction yield. The particle size, had a great effect on the maximum oil extracted yields. The maximum yield of oil extraction using pure hexane (35%), while for pure ethanol, the maximum yield of the oil extraction (45%) for the solvent, by using the water-solvent mixture this percentage has significant increasing in water-hexane solvent system.